Sensitive interferometric detection of ultrasound for minimally invasive clinical imaging applications - Rosenthal, Amir; Kellnberger, Stephan; Bozhko, Dmitry; Chekkoury, Andrei; Omar, Murad; Razansky, Daniel; Ntziachristos, Vasilis (Laser & Photonics Reviews, 2014)
Miniaturized optical detectors of ultrasound represent a promising alternative to piezoelectric technology and may enable new minimally invasive clinical applications, particularly in the field of optoacoustic imaging. However, the use of such detectors has so far been limited to controlled lab environments, and has not been demonstrated in the presence of mechanical disturbances, common in clinical imaging scenarios. Additionally, detection sensitivity has been inherently limited by laser noise, which hindered the use of sensing elements such as optical fibers, which exhibit a weak response to ultrasound. In this work, coherence-restored pulse interferometry (CRPI) is introduced - a new paradigm for interferometric sensing in which shot-noise limited sensitivity may be achieved alongside robust operation. CRPI is implemented with a fiber-based resonator, demonstrating over an order of magnitude higher sensitivity than that of conventional 15 MHz intravascular ultrasound probes. The performance of the optical detector is showcased in a miniaturized all-optical optoacoustic imaging catheter. Miniaturized optical detectors of ultrasound represent a promising alternative to piezoelectric technology. In this work, coherence-restored pulse interferometry (CRPI) is introduced a paradigm for interferometric sensing in which shot-noise limited sensitivity may be achieved alongside robust operation. CRPI is implemented with a fiber-based resonator, demonstrating over an order of magnitude higher sensitivity than that of conventional 15 MHz intravascular ultrasound probes. The performance of the optical detector is showcased in a miniaturized all-optical optoacoustic imaging catheter. © 2014 by WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Imaging; Interferometry; Optoacoustics; Sensing; Ultrasound